Correlation-dependent tunneling of a ballistic particle - Villanueva, Anthony Allan D. (2015)
The tunneling probability of a ballistic particle project towards the classical turning point is determined a Gaussian wave packet with an initial position-momentum correlation. The tunneling probability is shown to temporarily decrease for a negative correlation parameter C. Such quantum states may possibly improve particle confinement in atomic traps with a linear potential component such as magnetic and gravitational cavities.
Keywords: Wave equation; Tunneling (Physics)